Kilogram Synthesis of (S)-3-Aminopyran from l-Glutamic Acid - Savage, Scott; Babu, Srinivasan; Zak, Mark; Mao, Zhongping; Cao, Jianhua; Ge, Yonghui; Ma, Dongxu; Jiang, Guoqiang (Synlett, 2013)
We describe the development of a concise route to prepare kilogram quantities of (S)-3-aminopyran, a key intermediate in the synthesis of a Jak1 inhibitor. The chiral amine was introduced via a chiral-pool approach and involves using inexpensive, commercially available l-glutamic acid as the key starting material. Global protection, followed by reduction afforded the N-Boc-amino diol. Intramolecular Mitsunobu cyclization and deprotection afforded the desired compound in 30% overall yield over four steps without the use of chromatography.
Keywords: aminopyran; Mitsunobu; intramolecular; cyclization; glutamic acid; chiral pool; diols